DIFFERENCES IN MOTOR ABILITIES BETWEEN KARATE ATHLETES AND NON-ATHLETES - Zoran Simonović; Saša Bubanj; Aleksandra Projović; Goran Kozomara; Radoslav Bubanj (Sport Scientific And Practical Aspects, 2025)
Since physical education is inadequately represented by the number of hours in a school curriculum, teaching approach is realized with the low energy component, which is a major problem in realization of program tasks. For this reason, there is an increasing number of children who are involved in the training process in sports clubs or sections of physical education in schools. The aim of actual research was to determine the motor abilities of subjects, i.e. karate athletes and non-athletes and determine if there is a statistically significant difference. The sample consisted of 52 subjects (24 karate athletes and 28 non-athletes), aged 11-12 years ± 6 months, regularly participating in the school physical education classes. Measuring instruments for motor abilities evaluation were the tests of: (1) explosive strength; (2) segment speed; (3) repetitive strength; (4) coordination. For the statistical analysis and interpretation of the results, the statistical package Statistics 8.0 was in use. Results were expressed by descriptive statistics, while in aim to calculate significant differences between mean values of motor abilities between karate athletes and non-athletes, T-test for small independent samples was in use. T-test results in relation to the motor abilities, showed statistically significant difference in favor of karate athletes in the tests of explosive strength i.e., standing long jump (MSDM .011), triple jump from the stationary position (MTRS .000) and quintuple jump from the stationary position (MPTS .000); repetitive strength i.e., trunk lifting on the Swedish bench (MDTK .000), mixed ups (MMZG .000) and squats (MČUČ .000) and in two tests of coordination i.e., agility in the air (MOKV .000) and coordination with the bat (MKOP .006). In order to assess and monitor the development of the motor abilities in children it is necessary to provide reliable data, which creates a good basis for the results at a later age, as well the basis for taking any corrective intervention in the practical realization of the exercise program.